2020
DOI: 10.1007/s10854-020-04246-1
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, fluorescence, filter, nano tribological and photoconductivity studies of 4-(4-chlorophenyl)-7,7-dimethyl-7,8-dihydro-4H-1-benzopyran-2,5(3H,6H)-dione (CPDMDHHBPHHD) macro and nano crystals

Abstract: The present investigation is focused on the macro and nanocrystals of 4-(4-chlorophenyl)-7,7-dimethyl-7,8-dihydro-4H-1-benzopyran-2,5(3H,6H)-dione (CPDMDHHBPHHD), its synthesis, and the various characterization and comparative studies performed to assess its applications. Nanocrystals were prepared by milling procedure and its evaluation and utility than macro-sized entitled crystals were thoroughly discussed. The single crystal XRD study reveals the macro-crystalline lattice parameters with the empirical form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The effective role of PPy is tried for electronic filters as the influx in microns for the opto-electronic filters and is 3.7873; 3.7874; 3.7874; 3.7874; 3.7874 and 3.7875 corresponding to MR values as 0.5; 1.0; 1.5; 2.0; 2.5 and 3 respectively, showed no much variations as samples are not anisotropic and are amorphous in nature; so, as the MR values [ [39] , [40] , [41] , [42] , [43] ] are getting elevated in esteem and for filters used in optoelectronic type, minor variations are seen and are also in fourth decimal places. Furthermore, in the burglar alarm to enhance the efficiency of the system, PPy coated components are 1.12, 1.13, 1.13, 1.13, 1.13 and 1.16 times efficient than the uncoated ones and are reducing the noise level due to fine homogeneous particles [ [43] , [44] , [45] , [46] , [47] , [48] ]. The IC-741 type of voltage doubling circuital portfolio represents double the value for normal case and is 2.01; 2.03; 2.03; 2.03; 2.03; 2.03 times for the versatile scaling MR values and confirmed the doubling of voltage in circuits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective role of PPy is tried for electronic filters as the influx in microns for the opto-electronic filters and is 3.7873; 3.7874; 3.7874; 3.7874; 3.7874 and 3.7875 corresponding to MR values as 0.5; 1.0; 1.5; 2.0; 2.5 and 3 respectively, showed no much variations as samples are not anisotropic and are amorphous in nature; so, as the MR values [ [39] , [40] , [41] , [42] , [43] ] are getting elevated in esteem and for filters used in optoelectronic type, minor variations are seen and are also in fourth decimal places. Furthermore, in the burglar alarm to enhance the efficiency of the system, PPy coated components are 1.12, 1.13, 1.13, 1.13, 1.13 and 1.16 times efficient than the uncoated ones and are reducing the noise level due to fine homogeneous particles [ [43] , [44] , [45] , [46] , [47] , [48] ]. The IC-741 type of voltage doubling circuital portfolio represents double the value for normal case and is 2.01; 2.03; 2.03; 2.03; 2.03; 2.03 times for the versatile scaling MR values and confirmed the doubling of voltage in circuits.…”
Section: Resultsmentioning
confidence: 99%
“…The IC-741 type of voltage doubling circuital portfolio represents double the value for normal case and is 2.01; 2.03; 2.03; 2.03; 2.03; 2.03 times for the versatile scaling MR values and confirmed the doubling of voltage in circuits. The mechanical representation of samples figuring out the proper projection of their hardness or softness and identifying it based on their value to tribological parameters and here, the hardness profile of MR as 0.5 is tried for Vicker's scale of 25, 50 and 100 g and their H V value in kg/mm 2 as 56.2; 68.6 and 97.9 and give rise to n as above 2 and is of Reverse Indentation Size Effect and other samples are in progress for analysis and are pelleted and analyzed [ [43] , [44] , [45] , [46] , [47] , [48] ]. The versatile method of the carbothermal way [ [49] , [50] , [51] , [52] , [53] ] is deliberately represented to proceed for PPy in the future with other typical studies [ 49 , [54] , [55] , [56] , [57] , [58] , [59] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic transition takes place in the specimen is properly identified with UV-vis spectrum by the absorbance data of 4B4CBA micro scaled one as in Fig. 3 and found that cut-off value is 389 nm and corresponding band gap by absorbance spectrum is 3.18 eV and the micro-photonic use of micro scaled 4B4CBA is analyzed as the 0-7 eV as hν data and (0-4*10 11 ) (αhν) 2 (cm −1 eV) 2 data in X and Y axis for the Tauc's classification of 4B4CBA plot as in Fig. 4 and found that it is 3.18 eV as the photonic band gap.…”
Section: Characterizationsmentioning
confidence: 96%
“…The NLO process needs materials that control the amplitude, optical beam frequency, phase and polarization. [2][3][4][5][6][7][8][9] Generally, most organic crystals possess their absorption in the visible blue region and some have their cutoff wavelength greater than 450 nm. This shows the possibility of a decrease in the conversion efficiency of the second harmonic generation (SHG) because of the self-absorption of the materials when using a semiconductor laser.…”
mentioning
confidence: 99%